Design of Fuzzy Keyword Search Engine (International Journal of Current Engineering and Technology, 2014)
This paper addresses to the design of fuzzy keyword search engine. In a fuzzy keyword search engine, in which if person try to search for the word gravity but by mistake he type graweety then also it show the result of gravity. In a fuzzy search engine it not rarely matter that exact word spelling, because fuzzy logic work on the partial truth, if some words of the search word is also matches it show the result. In fuzzy keyword search engine search for the synonyms word and also handle a singular plural condition. Now a day’s fuzzy logic is used in a various application.
Keywords: Fuzzy search engine, Fuzzy logic